AUTHOR'S APPROACH TO THE CONCEPT “FINANCING OF JOINT STOCK COMPANIES THROUGH STOCKS” (American Journal of Business Management, Economics and Banking, 2023)
The purpose of the author is to define the theoretical and economic essence of "financing of joint-stock companies through stocks." In the author's opinion, first of all, it is impossible to talk about financial indicators that reflect his position, without specifying "financing of joint-stock companies through stocks." Based on the results of the study, the author's definition was formulated for the concept of "financing joint-stock companies through stocks". The author provides a description of the financing of joint-stock companies, based on the strategic goals of joint-stock companies and sources of funding. Scientific conclusions on the topic were also made.